G protein-coupled estrogen receptor 1 regulates renal endothelin-1 signaling system in a sex-specific manner - Guthrie, Ginger L.; Almutlaq, Rawan N.; Sugahara, Sho; Butt, Maryam K.; Brooks, Craig R.; Pollock, David M.; Gohar, Eman Y. (Frontiers in Physiology, 2023)
Demographic studies reveal lower prevalence of hypertension among premenopausal females compared to age-matched males. The kidney plays a central role in the maintenance of sodium (Na+) homeostasis and consequently blood pressure. Renal endothelin-1 (ET-1) is a pro-natriuretic peptide that contributes to sex differences in blood pressure regulation and Na+ homeostasis. We recently showed that activation of renal medullary G protein-coupled estrogen receptor 1 (GPER1) promotes ET-1-dependent natriuresis in female, but not male, rats. We hypothesized that GPER1 upregulates the renal ET-1 signaling system in females, but not males. To test our hypothesis, we determined the effect of GPER1 deletion on ET-1 and its downstream effectors in the renal cortex, outer and inner medulla obtained from 12-16-wk-old female and male mice. GPER1 knockout (KO) mice and wildtype (WT) littermates were implanted with telemetry transmitters for blood pressure assessment, and we used metabolic cages to determine urinary Na+ excretion. GPER1 deletion did not significantly affect 24-hr mean arterial pressure (MAP) nor urinary Na+ excretion. However, GPER1 deletion decreased urinary ET-1 excretion in females but not males. Of note, female WT mice had greater urinary ET-1 excretion than male WT littermates, whereas no sex differences were observed in GPER1 KO mice. GPER1 deletion increased inner medullary ET-1 peptide content in both sexes but increased outer medullary ET-1 content in females only. Cortical ET-1 content increased in response to GPER1 deletion in both sexes. Furthermore, GPER1 deletion notably increased inner medullary ET receptor A (ETA) and decreased outer medullary ET receptor B (ETB) mRNA expression in male, but not female, mice. We conclude that GPER1 is required for greater ET-1 excretion in females. Our data suggest that GPER1 is an upstream regulator of renal medullary ET-1 production and ET receptor expression in a sex-specific manner. Overall, our study identifies the role of GPER1 as a sex-specific upstream regulator of the renal ET-1 system.